An evolutionary psychology perspective on athletic development and performance: differences between proximate and ultimate explanations - Baker, J.; Johnston, K. (Sports Medicine, 2025)
Many areas of mainstream psychology have embraced the notions that understanding human behaviour can be improved by integrating developments from evolutionary science; however, evolutionary principles have not been as widely applied among sport researchers or practitioners, especially those examining athlete development and the psychology of competition and performance. In this paper, we discuss the distinction between ultimate and proximate explanations of psychological outcomes, and the relevance of this distinction for exploring issues related to skill acquisition and athlete development. We use three examples—deliberate practice, early sport play and sustained engagement—to highlight the benefits and challenges of applying evolutionary theories to sport contexts. Embracing our species` evolutionary history has the potential to inform ongoing debates in athlete development and performance, among other areas of sport science.